Self-administered gerocognitive examination (SAGE) aids early detection of cognitive impairment at primary care provider visits - Scharre, Douglas W.; Vrettos, Nicole E.; Nagaraja, Haikady N.; Wexler, Randell K.; Clark, Aaron D.; Nguyen, Christopher M. (Frontiers in Medicine, 2024)
Current estimates indicate that up to 50%-75% of dementia cases are undiagnosed at an early stage when treatments are most effective. Conducting robust accurate cognitive assessments can be time-consuming for providers and difficult to incorporate into a time-limited Primary Care Provider (PCP) visit. We wanted to compare PCP visits with and without using the self-administered SAGE to determine differences in identification rates of new cognitive disorders. Methods: Three hundred patients aged 65-89 without diagnosed cognitive disorders completing a non-acute office visit were enrolled (ClinicalTrials.gov Identifier: NCT04063371).Two PCP offices conducted routine visits for 100 consecutive eligible patients each. One office used the SAGE in an additional 100 subjects and asked available informants about cognitive changes over the previous year. Chart reviews were conducted 60 days later. One-way analysis of variance and Fisher exact tests were used to compare the groups and outcomes. Results:When SAGE was utilized, the PCP documented the detection of new cognitive conditions/concerns six times (9% versus 1.5%) as often (p = 0.003). The detection rate was nearly 4-fold for those with cognitively impaired SAGE scores (p = 0.034). Patients having impaired SAGE score and informant concerns were 15-fold as likely to have new cognitive conditions/concerns documented (p = 0.0007). Among providers using SAGE, 86% would recommend SAGE to colleagues. Discussion: SAGE was easily incorporated into PCP visits and significantly increased identification of new cognitive conditions/concerns leading to new diagnoses, treatment, or management changes. The detection rate increased 15-fold for those with impaired SAGE scores combined with informant reports.